Accuracy and reproducibility of shear wave elastography according to the size and elasticity of lesions: A phantom study. Issue 41 (14th October 2022) - Kim, Harim; Kim, Haejung; Han, Boo-Kyung; Choi, Ji Soo; Ko, Eun Sook; Ko, Eun Young
Abstract : While the extrinsic factors affecting reproducibility of shear wave elastography (SWE) have been well documented, there are few resources assessing intrinsic characteristics of the lesion affecting the reproducibility and accuracy of SWE. In this regard, this study aimed to evaluate the accuracy of measured elasticity and the reproducibility of SWE according to the lesion size and stiffness. Two breast radiologists examined 20 targets of 4 different levels of stiffness and 5 different sizes (2.5, 4, 7, 11, and 18 mm) in a customized elasticity phantom. The B-mode image, color elastography image, and kPa measurement were obtained twice by each examiner with a 1-week interval. Inter- and intra-observer reproducibility and the accuracy of measured kPa were analyzed using intraclass correlation coefficient (ICC) and Bland-Altman analysis. Subgroup analysis was run to evaluate the effect of lesion size and stiffness on the reproducibility and accuracy of measured kPa. Inter- and intraobserver reproducibility for measuring kPa showed excellent agreement (ICC: 0.9742 and 0.9582; ICC: 0.9932 and 0.9294). The size and stiffness of the targets did not affect reproducibility. The overall accuracy of measured kPa was very high (ICC: 0.8049). In the subgroup analysis, targets that were ≤4 mm in size showed lower accuracy (ICC: 0.542), whereas targets that were 7 and 11 mm in size showed higher accuracy (ICC: 0.9832 and 0.9656, respectively). SWE shows excellent reproducibility regardless of lesion size or stiffness in phantom targets. The accuracy of measured kPa is high in lesions that are 7 and 11 mm in size but is low in lesions that are ≤4 mm in size.